2021
DOI: 10.1111/exsy.12834
|View full text |Cite
|
Sign up to set email alerts
|

The role of contemporary digital tools and technologies in COVID‐19 crisis: An exploratory analysis

Abstract: Following the Covid‐19 pandemic, there has been an increase in interest in using digital resources to contain pandemics. To avoid, detect, monitor, regulate, track, and manage diseases, predict outbreaks and conduct data analysis and decision‐making processes, a variety of digital technologies are used, ranging from artificial intelligence (AI)‐powered machine learning (ML) or deep learning (DL) focused applications to blockchain technology and big data analytics enabled by cloud computing and the internet of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…The data acquisition of our survey was finished before the world was struck by the COVID-19 pandemic, which caused a significant boost of digitalization of the health system as well as of the working and everyday life. 78 Further studies will be necessary to address questions about the impact of the global pandemic on the perception of AI in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…The data acquisition of our survey was finished before the world was struck by the COVID-19 pandemic, which caused a significant boost of digitalization of the health system as well as of the working and everyday life. 78 Further studies will be necessary to address questions about the impact of the global pandemic on the perception of AI in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…✓ Subramanian et al, (2021) made a compherensive literature review by using secondary data and information.…”
Section: Selecting Articlesmentioning
confidence: 99%
“…While smart technologies such as artificial intelligence, machine learning, and deep learning are employed in healthcare facilities to manage resources and services, robots and drones help limit the spread of Coronavirus by minimizing interpersonal interaction. (Subramanian et al, 2021). Table 2 presents the smart healthcare logistics practices during pandemic.…”
Section: Content Analysismentioning
confidence: 99%
“…It is reported that emerging technologies such as augmented reality (AR), artificial intelligence (AI) as well as its branches of machine learning (ML), and deep learning (DL) have solved quite a few problems related to disease management and nursing, especially since the outbreak of COVID-19. 3 There is a great possibility that DL & AR can be the backbone of implementing intelligent nursing due to its outstanding performance in meeting patients' demands.…”
Section: Introductionmentioning
confidence: 99%